Constituting the 'sexually violent predator': Law, forensic psychology, and the adjudication of risk. (November 2019) - Vogler, Stefan
Considerable socio-legal scholarship demonstrates law's constitutive power, and much criminological research has considered the effects of actuarial risk assessment. However, these strands have rarely been brought together to consider how legal risk assessment practices constitute sexual subjects. This article argues that law and forensic psychology co-constitute the category of the 'sexually violent predator' (SVP) as a distinct type of person through the use of psychiatric diagnosis and actuarial risk assessment. Contrary to dominant views of actuarialism as de-individualizing, this article asserts that SVP proceedings are centrally concerned with individualized intervention, yet such proceedings continue to produce static risk subjects rather than the dynamic subjects identified in recent research on actuarial practices. It is argued that this stems from entrenched cultural views of sexuality as a fixed essence inherent in individuals. The risk assemblage in SVP proceedings therefore presents a unique theoretical case that does not clearly fit prevailing accounts of actuarialism.